The drilling of an Al/SiCp metal-matrix composites.: Part 1 - Tosun, G; Muratoglu, M (Elsevier Sci Ltd, 2004)
Automotive, aircraft and train companies need to replace steel and cast iron in mechanical components with lighter high strength alloys like Al metal matrix composites (MMC). Despite the superior mechanical and thermal properties of particulate metal matrix composites, their poor machinability is the main deterrent to their substitution of metal parts. Machining is a material removal process and therefore is important for the final fabrication stage prior to application. Consequently the development of effective machining methods, leading to a reduction in the overall cost of components, is one of the major challenges yet to be solved. In this study, the influence of the type of drills, point angles of drills and ageing on the drilling performance of 2124 aluminum alloy reinforced with 17% SiC particulates was investigated experimentally. The workpiece material was drilled in four heat treatment conditions: as-received, solution treated, and solution treated and aged for 4 and 24 h. The experimental studies were conducted under different settings of spindle-speed and feed rate and point angles of drill. Drilling tests were carried out using high-speed steel (HSS), TiN coated HSS and solid carbide drills. The drills used were 5 mm diameter. The experimental results indicated that, the effect of point angles on the sub-surface damage caused by the drilling operation was changed with the type of drills. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: metal matrix composites; drilling; microstructure